Theological Reflection in Adolescent Faith Formation: Sociological, Psychological, and Theological Perspectives - Garcia, Fernando (Journal of youth and theology, 2023)
Christians are increasingly choosing to leave the church during the period of young adulthood. This trend suggests that there are shortcomings in our practices of religious education and faith formation. Here I propose that the practice of theological reflection is a method that can be employed to address some of these shortcomings. The article connects trends of religious disaffiliation with psychological theories of identity formation and self-determination that shed light on the internal changes leading young people away from religion. Theological reflection, the process of examining one’s experience through the lens of religious teachings, is a common practice in the formation of Church ministers and has potential to also benefit the faith formation of adolescents. With consideration of the psychological patterns related to disaffiliation, I demonstrate ways that theological reflection can foster a Christian identity in students that has an enduring impact on the lives of adolescents and young adults.